Ethnic Variations in Perception of Human Papillomavirus and its Vaccination among Young Women in Nepal - Sathian, Brijesh; Babu, MG Ramesh; van Teijlingen, Edwin R; Banerjee, Indrajit; Roy, Bedanta; Subramanya, Supram Hosuru; Rajesh, Elayedath; Devkota, Suresh (Nepal Journal of Epidemiology, 2017)
Background: The Human Papillomavirus (HPV) is strongly associated with cervical and other cancers. In women, cervical cancer is the third most common cancer. HPV infection can be largely prevented through vaccination of (adolescent) girls. At the same time, Nepal is a low-income country experiencing a cultural change in attitudes towards sex and sexual behaviour. However, in the adolescent population knowledge about HPV, factors associated with an increased risk of HPV and the existence of the vaccination is often low. Materials and Methods: This was a cross-sectional study with female students enrolled in health and non-health science courses in Pokhara, Nepal. The questionnaire included demographic details, knowledge and attitude questions related to HPV, associated risk behaviour and its vaccination. Descriptive statistics, including Chi-Square test, were used to identify statistically significant relationships. Ethical approval was granted by the relevant authority in Nepal. Results: Hindu religion (75.0 %; 95% CI: 70.9, 78.6) and Newari caste (75.5%; CI: 61.1, 86.7) were more aware about HPV, HPV vaccination. Hindus religion (55.6%; 95% CI: 51.2, 60.0) and Dalit caste (61.6%, 95% CI: 53.3, 69.4) more willing to be vaccinated than other religions and other castes, respectively. Not unsurprisingly, students on health-related courses had a greater awareness of HPV, HPV vaccination and were more willing to be vaccinated than students on other courses. Similar patterns of association arose for knowledge related to those sexually active at an early age; HPV risk and multiple sex partners; and fact that condoms cannot fully prevent the transmission of HPV. Conclusion: Knowledge about the link between HPV and (a) early sexual initiation, (b) having multiple sexual partners, and (c) the limited protection of condoms and other birth control measures was poor in our study compared to similar research conducted in other parts of the world. One key implication is the need for education campaigns in Nepal to educate young women and their parents about HPV, its risk factors and the benefits of vaccination.